An unusual case of complete pathological response to Paget's disease of the breast. Issue 4 (11th April 2022) - Okonofua, Daisy; Soh, Chien Lin; Tafazal, Habib
Abstract: Mammary Paget's disease is a rare form of breast cancer present in 0.5–2.8% of breast cancers. The patients have a poorer prognosis, and usually, the appropriate therapy is based on the pathologic findings of the mass and axillary staging. This report adds the outcomes of Paget's disease following neoadjuvant chemotherapy to the literature by description of a case of a 48-year-old patient with Paget's disease who had a complete pathological response to Paget's disease of the breast following neoadjuvant chemotherapy.